A study on pattern of placentation in post caesarean pregnancy - S., Deepthi P.; Devasia, Neena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: It appears that the rate of caesarean delivery has been increasing over the past two decades. Various western studies have shown that with previous caesarean section, increased risk of placenta previa, adherent placenta, and greater incidence of antepartum haemorrhage. Nonetheless, the extent to which previous caesarean delivery predisposes women to the development of placenta previa is unclear from earlier studies. Also, there are not many Indian studies regarding the association of placenta previa and previous caesarean section. This study aims to find the association between prior caesarean delivery and subsequent development of placenta previa and adherent placenta. Methods: A descriptive study was conducted on 600 antenatal women with post cesarean pregnancy in a tertiary care centre. Similar number of women with previous normal delivery was included in comparison group and placental location was studied. Those patients with previous caesarean were further divided into those with placenta previa and without previa to study the determinants of previa in those with previous caesarean section. Results: Placenta previa was found in 2.8% of the study group compared to 1.2% of comparison group. Adherent placenta was found only in post caesarean group. In the post caesarean group, the incidence of anterior previa was 41.2% compared to posterior previa (29.3%). In those with post cesarean pregnancy, determinants of placenta previa found were multiparity (35.3%), previous history of abortions (35%), multiple previous caesarean sections (29.4%), interpregnancy interval <2 years (35.29%). Conclusions: In post cesarean pregnancy, the risk of placenta previa is 2 times compared to those with a previous normal delivery. Anterior previa occurred with sufficient frequency in post-caesarean pregnancy to warrant ultrasonic placentography prior to surgical entry into lower segment. When the combination of previous caesarean and placenta previa occurs the risk of adherent placenta is 17.6%.